PHYSICAL AND THERMAL PROPERTIES OF RUBBER GLOVE WASTE AS POTENTIAL FILLER FOR POLYMER COMPOSITES - Nuzaimah, M.; Sapuan, S.M.; Nadlene, R.; Jawaid, M.; Rashid, B. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
A serious threat of the rising rubber waste globally has made researchers extensively look for an alternative to recycle it. Rubber waste is difficult to degrade due to its highly cross-linked structure that can lead to pollution and spreading of diseases. Rubber waste is very elastic and possess high durability behaviour which potentially can provide enhancement towards the composite properties. In this work, rubber waste was obtained from discarded rubber gloves and went through cryogenic grinding to produce crumbs. The glove waste was soaked in liquid nitrogen until frozen and grounded using crusher. The crumbs were later analysed by using physical and thermal characterisation methods. The sizes of the rubber crumbs were determined by using sieving method and ranging from 300 µm to 2 mm. The shape of the crumbs and their surface details were observed by using a scanning electron microscope (SEM) and thermal analysis was conducted by using thermogravimetric analysis (TGA). The microscopy showed the rubber crumbs has regular shapes and smooth surfaces. The thermogravimetric results revealed both waste and fresh rubber crumbs degraded in the same manner. They degrade in three stages and obvious mass loss occurred between 250 ºC to 400 ºC due to degradation of the main natural rubber element; poly-cis-1,4-isoprene. In comparison to fresh rubber crumb, thermal behaviour of waste rubber crumbs remains the same. Thus, the properties of waste rubber are still similar to fresh rubber crumbs. Consequently, on the basis of properties obtained from this work, the rubber waste crumbs acquired from rubber waste glove shows great potential to be used as a filler for the polymer composites.